ReiseRecht aktuell : Zeitschrift für das Tourismusrecht (Verlag Dr. Otto Schmidt, 1993)
RRa - ReiseRecht aktuellJournal for tourism lawThe RRa - your guide for the law of travel and tourismThe RRa journal informs you fast and reliably about all important areas of travel and tourism law, tourist travel contracts, general terms and conditions, contracts concerning carriage by air and by train as well as of law of insurance and competition law. Whether essays, court decisions or case notes - RRa puts it in a nutshell: Professionally condensed court decisions, concise case notes and easy to follow essays keep you informed about the most essential developments of law of travel and tourism. The RRa journal is, therefore, indispensable for everyone concerned with this important area of law.